The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.11606/s1518-8787.2018052000340
|View full text |Cite
|
Sign up to set email alerts
|

Private dental insurance expenditure in Brazil

Abstract: OBJECTIVE To quantify the household expenditure per capita and to estimate the percentage of Brazilian households that have spent with dental insurance.METHODS We analyzed data from 55,970 households that participated in the research Pesquisa de Orçamentos Familiares in 2008–2009. We have analyzed the annual household expenditure per capita with dental insurance (business and private) according to the Brazilian states and the socioeconomic and demographic characteristics of the households (sex, age, race, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Although Brazil has a large, free public health system, employed individuals are targeted by private health insurance companies. Regulation of the private health system began a few decades ago, and still needs to be improved to the extent that public services will no longer provide free services to private health insurance companies, 32 as has already occurred in Chile, Argentina and Colombia 33 . Unlike Brazil, other countries have private health insurance systems that are closely controlled by the federal government 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Although Brazil has a large, free public health system, employed individuals are targeted by private health insurance companies. Regulation of the private health system began a few decades ago, and still needs to be improved to the extent that public services will no longer provide free services to private health insurance companies, 32 as has already occurred in Chile, Argentina and Colombia 33 . Unlike Brazil, other countries have private health insurance systems that are closely controlled by the federal government 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Again, R$5.10 is spent on dental insurance of the total dental care expenditure and of this amount R$4.70 was for private dental coverage. Nonetheless, only 2.5% of Brazilians spend money on dental insurance [187]. Another study reported that in Brazil dental care is traditionally based on private dental service [188].…”
Section: Morbidity Mortality and Increase Healthcare Cost In Denmentioning
confidence: 99%
“…Moreover, it should be noted that in Brazil, it is estimated that at least 80% of the population depends exclusively on public dental care 15,32 , which, compared to the subsidized Finnish population, would be the most severely affected, in-creasing oral health disparities. Considering that the Finnish government postponed plans to extend health insurance to cover dental services for the entire adult population due to economic constraints 18 , one can assume that oral health is often outside the list of governments' priorities, when it comes to ensure the access of their populations to health care.…”
Section: Main Results Conclusionmentioning
confidence: 99%